al-Tarikh al-siyasi wa-al-thaqafi li-qabilah Shahran al-'aridah fi-al-jazirah al-'arabiyah ma bayn 560M-661M : dirasat tarikhiyah naqdiyah = Political and cultural history of Shahran Al-Arabian tribe in the Arabic Peninsula between 560M-661M : a historical study / Ali Saad M Alshahrani - Alshahrani, Ali Saad M (2013)
This is a study on one of the most famous Arab tribes in the Arabian Peninsula, which is the tribe of Syahran al-‘Aridah during the time of Prophet Muhammad and the time of the Rightly Guided Caliphs. This topic has rarely been discussed among scholars, although there is significance anthropological and historical elements, due to the fact that is continues to be the main foundation of the Saudi Arabs, as it was once was, and in fact the tribe was considered to be the primer tribe of the Arab society. This study will answer the question of the structure and size of the tribe of Syahran al-‘Aridah from the historical aspect, as well as studying its influence on the events that took place and developed during that time. This study will apply the descriptive method and historical comparison in order to study issues relating to the tribe’s history in terms of economy, sociology and culture during the jahiliyyah time and the coming of Islam. This study will also discuss the role of this tribe in the political play in the Arabian Peninsula in the early days of Islam, and their participation in the new entity, as well as their political contribution during the opening of Islamic nations, wars during the time of fitna, and their cultural contribution in the development of new Islamic nations. Towards the end of this study, a more detailed discussion on the political, societal and cultural life of this tribe is included as it mirrored the life of tribal life in the early days of Islam, and its contribution in the building of Islamic nations, which proved its contributions in the building of civilizations in the history of Islam and Arabian Peninsula.